Pengaruh ROA dan EPS Terhadap Harga Saham Sektor Consumer Non-Cyclical ISSI Tahun 2023: Perspektif Keseimbangan Umum - Keysya Muyasaroh Khasanah; Rara Presila; Suci Hayati (Indo Publishing, 2025)
The objective of this study is to evaluate how Return on Assets (ROA) and Earnings Per Share (EPS) affect the share value of the Indonesia Shariah Stock Index (ISSI) non-cyclical consumer sector in 2023, using general equilibrium methodology. This sector was chosen due to its resilience to economic fluctuations and significant contribution to the Islamic capital market. This study uses an explanatory quantitative approach utilising financial statement data from the companies, with analysis conducted through multiple linear regression. The results show a significantly positive impact of EPS on share price, while ROA has an adverse impact, highlighting that investors prioritise earnings per share over asset utilisation. The general equilibrium viewpoint illustrates how the interaction of key factors drives stability in the Islamic stock market, providing suggestions for investors and policy makers in advancing the Islamic capital market.